2015
DOI: 10.1177/0394632015572083
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ginger and zinc chloride mixture on the liver and kidney alterations induced by malathion toxicity

Abstract: This study was carried out on four groups of male Wistar rats, 10 rats per group. Group I got open access to food intake and water with normal balanced diet. Group II was administered 400 mg ginger per kg body weight (BW) and zinc chloride (ZnCl2) (300 mg/L) diluted in tap water for 4 months. Group III was administered malathion at a dose of 50 mg/kg BW/day in 0.2 mL corn oil via gavages for 4 months. This dose equal to 1/50 of the LD50. Group IV was given a mixture of 400 mg ginger per kg BW and ZnCl2 (300 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…MAL may represent a greater risk than it would be expected. The toxicity of malathion is highly correlated with its metabolites and affected by MAL contaminants (Baiomy et al 2015). Therefore, with the aim to understand MAL toxicity, we first have to understand the pharmacokinetics of MAL, as well as its pharmacodynamics.…”
Section: Malathion Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…MAL may represent a greater risk than it would be expected. The toxicity of malathion is highly correlated with its metabolites and affected by MAL contaminants (Baiomy et al 2015). Therefore, with the aim to understand MAL toxicity, we first have to understand the pharmacokinetics of MAL, as well as its pharmacodynamics.…”
Section: Malathion Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…A lot of protective natural compounds had been found for their neuroprotective properties in preventing diseases and inflammation [ 1 , 2 , 3 , 4 ]. Chili peppers have become a vital part of culinary cultures worldwide and have a long history of use for flavoring, coloring, and preserving food, as well as for medical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that increase of creatinine occurred with renal failure (Hayes, 1994). Previous investigations showed a significant enhancement of blood creatinine, urea and uric acid levels, and renal histological changes in experimental animals exposed to malathion and other pesticides (Al-Attar, 2015;Baiomy et al, 2015;Kanbur et al, 2016;Li et al, 2016;Kaya et al, 2018;Muhammad et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…One of the main toxic effects of malathion on the central nervous system is related to the inhibition of acetylcholinesterase (AChE) activity, which produces acute hypercholinergic syndrome (Kwong, 2002). Moreover, previous experimental investigations showed that malathion induced various biochemical and histological changes in experimental animals (Baiomy et al, 2015;Abdel-Salam et al, 2018;Gupta et al, 2019;Hosseini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%